Persistence of the efficacy of copper oxide wire particles against Haemonchus contortus in grazing South African goats - Vatta, A.F.; Waller, P.J.; Githiori, J.B.; Medley, G.F. (Elsevier, 2012)
A study was conducted to examine the duration of anthelmintic effect of copper oxide wire particles (COWP) in grazing goats, as data for the persistence of efficacy of COWP in this host species is limited. Forty-eight indigenous male goats were infected naturally by grazing them on Haemonchus contortus-infected pasture. When the faecal egg count (FEC) in the goats was 3 179 ± 540 eggs per gram of faeces (mean ± standard error), half the animals were treated with 4 g COWP (day 0; mean live weight = 25.5 ± 0.8 kg). Eight treated (COWP) and eight non-treated (CONTROL) goats were removed from the pasture on each of days 7, 28 and 56, maintained for 27 or 29 days in concrete pens and then humanely slaughtered for nematode recovery. Mean liver copper levels were in the high range in the goats removed from pasture at day 7 (treated: 191 ± 19.7 ppm; untreated: 120 ± 19.7 ppm; P = 0.022), but had dropped to normal levels at days 28 and 56. The mean H. contortus burdens of the treated versus the non-treated goats were, respectively, 184 ± 48 and 645 ± 152 for the goats removed from pasture at day 7 (71% reduction; P = 0.004), 207 ± 42 and 331 ± 156 at day 28 (37% reduction; P = 0.945) and 336 ± 89 and 225 ± 53 at day 56 (-49% reduction; P = 0.665). Weekly monitoring of FECs after treatment until slaughter indicated that the COWP-treated goats had lower FECs than the controls, the treatment main effect being significant at days 7, 28 and 56 (P < 0.01). The day main effect and the treatment x day interaction were only significant for the goats removed from pasture at day 28 (P ≤ 0.001). Packed cell volumes increased during the course of the experiment (day, P < 0.001), but the treatment main effect was significant only for the goats removed from pasture at day 28 (CONTROL 28 d, 28.65 ± 0.52% < COWP 28 d, 31.31 ± 0.52%; P < 0.001). No differences in live weight between groups were considered to be of any practical significance. The study indicated that persistence of efficacy of COWP is limited in goats, extending at most to 28 days after treatment. However, repeated COWP administration at three-month intervals may be safe, given that liver copper levels return to normal two to three months after COWP treatment.